Applications of Generative AI and Large Language Models in network and cloud security - Nadtochyi, M. M.; Balagura, D. S. (ХНУРЕ, 2025)
The aim of the paper is to analyze theory and practice of GenAI and LLM applications in network and cloud security.
Keywords: Generative AI; Large Language Model